Konsepsi Tentang Kebijakan Hukum Terbuka (Open Legal Policy) Pembentuk Undang-Undang Pasca Putusan Mahkamah Konstitusi Nomor 62/Puu-XXII/2024: Analisa Terhadap Pembatasan Kekuasaan Sebagai Inti Dari Paham Konstitusionalisme - Delfina Gusman (Jurnal Sakato Ekasakti Law Review, 2026)
Constitutional Court Decision Number 62/PUU-XXII/2024 which granted the request for judicial review of the 1945 Constitution of the Republic of Indonesia regarding the presidential threshold (threshold for nominating President and Vice President) stated in the provisions of Article 222 of Law Number 7 of 2017 "Candidate pairs are proposed by political parties or coalitions of political parties participating in the election that meet the requirements of obtaining seats of at least 20% (twenty percent) of the total number of seats in the DPR or obtaining 25% (twenty five percent) of valid votes nationally in the previous DPR member election". In its decision, it was stated that the norm of Article 222 of Law Number 7 of 2017 is contrary to the 1945 Constitution of the Republic of Indonesia (unconstitutional) and has no binding legal force. The decision contradicts several previous Constitutional Court decisions regarding the same object, where the norm of Article 222 of Law Number 7 of 2017 was declared constitutional on the grounds that the norm was categorized as an open legal policy of lawmakers, one of which can be found in Constitutional Court Decision Number 73/PUU-XX/2022. . The formulation of the problem in this study is: 1) What is the concept of open legal policy of lawmakers before and after Constitutional Court Decision Number 62/PUU-XXII/2024? 2) What is the ideal conception in interpreting open legal policy of lawmakers based on the principle of limiting the power of lawmakers contained in the 1945 Constitution of the Republic of Indonesia? This research is a legal research, through a statute approach, a comparative approach, and a conceptual approach.